Proximal and mineral composition of native fish species from Amazonas, Brazil - Souza, Antônio Fábio Lopes de; Silva, Antonio José Inhamuns da; Barai, Alexandre Augusto; Rufino, João Paulo Ferreira; Costa, Tiago Viana da (Acta Scientiarum. Animal Sciences, 2023)
For decades, researches were developed about the diversity of fishes in the Amazon basin and their consumption by the people. In this context, an important gap identified was a lack of information about the nutritional composition of some of the main Amazon fish species consumed and traded. Front this, the objective of this study was to evaluate the chemical composition and mineral content of filets from 10 fish species with the highest landing volume in Amazonas State. The fish species selected were curimatã, jaraqui, mapará, matrinxã, pacu, piramutaba, sardinha, surubim, tambaqui and tucunaré. Were collected 20 samples (fishes) from each species according to the hydrological cycles of the region (20 samples in the flood and 20 samples in drought). Ten fish samples were processed to determine the proximal composition and 10 fish samples were used to determine mineral content (macro and micro minerals). The proximal composition of fish species analysed varied widely between species and seasons, with an emphasis on moisture and lipid content. Fishes in the flood season presented higher content of nutrients than drought season. This result also was observed in the minerals profile, where fishes in the flood season presented the highest (p < 0.05) minerals content.